A screening instrument for side dominance in competitive adolescent alpine skiers - Westin, M.; Norlén, A.; Harringe, M. L.; Werner, S. (Frontiers in Sports and Active Living, 2022)
Previous research has shown that high school ski students injure their left anterior cruciate ligament (ACL) more often than their right ACL, and that a prevention program focusing on equal load to the right and left ski turns prevents ACL injuries. Whether the injuries were in the dominant or non-dominant side of ski students was not determined but may be important knowledge to ski coaches for future design of ski-specific training programs. There is no gold standard on how to investigate the dominant side of alpine skiers. Therefore, the aim of this study was to develop a screening instrument consisting of five questions for identifying side dominance and to evaluate side dominance in competitive adolescent alpine skiers. First, 121 competitive adolescent alpine skiers answered the questions on side dominance using a test-retest design. The questions were: which hand/arm (left/right) or foot/leg (left/right) one uses as the first choice when writing, throwing, kicking a ball, jumping over a fence and stair-climbing. A question about safer/better ski turn to the left or to the right was also added. Second, 274 skiers answered the questions at one occasion. A very good agreement was shown in writing and throwing and kicking a ball, and a fair agreement was shown in jumping over a fence and stair climbing. A total of 243 skiers reported right-sided dominance, and seven skiers reported left-sided dominance. One hundred and nineteen of the 121 skiers who took part in the test-retest design answered the question safer/better ski turn, and of those 70 (59%) reported that they had a safer/better ski turn to one side than to the other side. However, the side was not consistent between the two test occasions, and the question did not correlate with side dominance. A combination of the three questions "What hand/arm do you use as first choice when writing?" "What hand/arm do you use as first choice when throwing?" and "What foot/leg do you use as first choice when kicking a ball?", may be used to decide side dominance in adolescent alpine skiers. Most adolescent alpine skiers reported right-sided dominance.